Responsive Hydrogels Based on Triggered Click Reactions for Liver Cancer - Zhu, Jia‐Qi; Wu, Han; Li, Zhen‐Li; Xu, Xin‐Fei; Xing, Hao; Wang, Ming‐Da; Jia, Hang‐Dong; Liang, Lei; Li, Chao; Sun, Li‐Yang; Wang, Yu‐Guang; Shen, Feng; et al. (Advanced materials (Weinheim), 2022)
Globally, liver cancer, which is one of the major cancers worldwide, has attracted the growing attention of technological researchers for its high mortality and limited treatment options. Hydrogels are soft 3D network materials containing a large number of hydrophilic monomers. By adding moieties such as nitrobenzyl groups to the network structure of a cross‐linked nanocomposite hydrogel, the click reaction improves drug‐release efficiency in vivo, which improves the survival rate and prolongs the survival time of liver cancer patients. The application of a nanocomposite hydrogel drug delivery system can not only enrich the drug concentration at the tumor site for a long time but also effectively prevents the distant metastasis of residual tumor cells. At present, a large number of researches have been working toward the construction of responsive nanocomposite hydrogel drug delivery systems, but there are few comprehensive articles to systematically summarize these discoveries. Here, this systematic review summarizes the synthesis methods and related applications of nanocomposite responsive hydrogels with actions to external or internal physiological stimuli. With different physical or chemical stimuli, the structural unit rearrangement and the controlled release of drugs can be used for responsive drug delivery in different states. Cross‐linked hydrophilic polymer chains that can form gels are widely utilized for biomedical applications, such as drug delivery. Various studies have also demonstrated the effects of particle size and surface morphology on drug release from particles in liver cancer therapy. Mechanistic understandings of responsive hydrogels in responsive stimuli are provided, by which better clinical choices may be approached.